Effect of Apolipoprotein E4 on the Driving Behavior of Patients with Amnestic Mild Cognitive Impairment or Mild Alzheimer's Disease Dementia - Stanitsa,E.; Economou, A.; Beratis,I.; Kontaxopoulou,D.; Fragkiadaki,S.; Papastefanopoulou,V.; Pavlou,D.; Papantoniou,P.; Kroupis, C.; Papatriantafyllou,J.; Stefanis,L.; Yannis,G.; et al. (J.Alzheimers.Dis., 2021)
BACKGROUND: The driving behavior of patients with mild Alzheimer's disease dementia (ADD) and patients with mild cognitive impairment (MCI) is frequently characterized by errors. A genetic factor affecting cognition is apolipoprotein E4 (APOE4), with carriers of APOE4 showing greater episodic memory impairment than non-carriers. However, differences in the driving performance of the two groups have not been investigated. OBJECTIVE: To compare driving performance in APOE4 carriers and matched non-carriers. METHODS: Fourteen APOE4 carriers and 14 non-carriers with amnestic MCI or mild ADD underwent detailed medical and neuropsychological assessment and participated in a driving simulation experiment, involving driving in moderate and high traffic volume in a rural environment. Driving measures were speed, lateral position, headway distance and their SDs, and reaction time. APOE was genotyped through plasma samples. RESULTS: Mixed two-way ANOVAs examining traffic volume and APOE4 status showed a significant effect of traffic volume on all driving variables, but a significant effect of APOE4 on speed variability only. APOE4 carriers were less variable in their speed than non-carriers; this remained significant after a Bonferroni correction. To further examine variability in the driving performance, coefficients of variation (COV) were computed. Larger headway distance COV and smaller lateral position COV were observed in high compared to moderate traffic. APOE4 carriers had smaller speed COV compared to non-carriers. CONCLUSION: The lower speed variability of APOE4 carriers in the absence of neuropsychological test differences indicates reduced speed adaptations, possibly as a compensatory strategy. Simulated driving may be a sensitive method for detecting performance differences in the absence of cognitive differences
IS - 1875-8908 (Electronic) IS - 1387-2877 (Linking) LA - eng PT - Journal Article RN - 0 (Apolipoprotein E4) SB - IM
Keywords: Adverse effects; Aged; Aged,80 and over; Alzheimer Disease; Amnesia; Apolipoprotein E4; Automobile Driving; Blood; Cognition; Cognitive Dysfunction; Complications; computer simulation; genetics; Genotype; Greece; Humans; Middle Aged; Neuropsychological Tests; psychology; Reaction Time; Risk Factors